Credit conditions and firm investment: Evidence from the MENA region - Risto Herrala; Rima Turk-Ariss (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
The Arab Spring is a clear indicator of the urgency of achieving inclusive growth and ensuring job creation in the Middle East and North Africa (MENA) region, where private sector development is still hindered by limited access to credit. Following Kiyotaki and Moore's (1997) seminal model, we apply a novel methodological approach to a unique data set of MENA firms to estimate credit limits and their impacts on capital accumulation. Notably, we find higher credit limits in countries where the Arab Spring erupted than in other MENA countries and that their marginal effect on capital accumulation has been statistically and economically significant.
URN:NBN:fi:bof-201408071955
Keywords: G31; L20; O16; 330; financing constraints; credit limits; MENA countries